Pelatihan Media Pemasaran Batik Berbasis Website pada Pengrajin Batik Kampung Kelembak Kota Batam - Friadi, John; Satriawan, Bambang; Windayati, Diana Titik; Yantri, One (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: Promotion and marketing methods for Batik Kelembak are currently carried out conventionally and are limited, ineffective, inefficient, and costly. and very limited time. Promotion and marketing based on digital marketing with a website as a promotional and marketing medium for Batik Kelembak is the right solution because promotion and marketing can reach wider locations, is effective, efficient, can reduce costs, is not limited by space and time and can be done anywhere and at any time just take a longer time. Methodology: Community service activities were implemented in November 2024. Community service activities were implemented in Kelembak Village, Nongsa District, Batam City. This community service activity is in the form of socialization and training by providing an understanding of the importance of digital promotions and marketing websites. The implementation method in the Community Service Program includes the survey, website creation, socialization and training, evaluation, mentoring, and reporting program implementation program as a whole. Results: The Kelembak village community can carry out promotions and marketing through future business development by using a web-based digital marketing strategy for their batik products so that it can explore the sale of batik products locally, and national and international answers to the challenges of the global economy. (John, 2022). Limitation: The expansion of market reach is expected to increase the potential sales of more humidity batik products, so that the income earned becomes maximum. When income increases, the people of Kelembak village will be better able to maintain the continuity of their business and help improve the economy in Indonesia. Contribution: Digital marketing can help the Kelembak village community expand the market to promote and market moisture batik products and open the insight of the people of Kelembak village to be more motivated to produce and develop their business with a broader reach.